L'utilizzo del GIS nell'analisi delle patologie di degrado. Nuove opportunità per la tutela del patrimonio culturale - Francesco Miraglia (Archeomatica, 2017)
The goal of this study is to describe the use of GIS to analyze and organize the degradation patterns of natural and artificial stones, according to the recommendations of the “Ente Italiano di Unificazione”, contained in the lexicon “UNI 11182/2006”. The use of GIS in the management of these information is an action of considerable scientific interest.